Implementasi Nilai Nilai Pancasila dalam Kehidupan Kampus - Ajeng Nafisya Raihan Malik; Junika Ferdila; Charel Zhalsadilla Haqni; Intan Nur Fadila; Anastasia Pratama Putri (Institut Nalanda, 2024)
A campus or higher education institution serves as an environment where students can acquire the knowledge, skills and experiences needed to grow and develop into competent individuals and make positive contributions to society. By applying the principles of Pancasila on campus, higher education institutions can create an environment that is welcoming, fair, and focused on building excellent student character. This can be done through the practice of gotong royong, democratic participation, respecting diversity, empowering communities, and upholding strong morality. Thus, the campus is not only a place to learn, but also a means to shape future generations who have integrity, tolerance, and high social awareness. The research aims to find out how the values of Pancasila are applied and implemented in various aspects of life on campus. The descriptive qualitative research method with a literature approach can also be understood as an approach in which researchers use written sources to describe and understand the phenomenon under study. The result of this research is that Pancasila values become an important foundation in shaping the character and attitude of students in the college environment.